THE SOCIAL ECONOMIC LIFE OF BANYUMAS RURAL COMMUNITY UNTIL THE XX CENTURY - Sukardi, Tanto (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
The reconstruction of social economic history in Banyumas in 1830-1900, has purpose to study the various factors which affect the social change in that region. This research uses theoretical frame, connected with the social change theory and the applicable method of history research through multidimensional approach, which related to the social and economic aspect. The historic research may be stated that the implementation of cultuurstelsel (enforcement planting or cultivation system) is the collaboration between West capitalism system with the traditional-feudalistic economy system, in order to exploitate the land and the workforce of the resident. The changes can be sectorial and partial, slow and non-comprehensive. In economic sector, the change is the distribution of money economy, which marked with the economy activities and the establishment of economy institution such as the credit service institution. While in the social sector, there is no new formation of social institution. However, some function dislocations in the society occur.